2001
DOI: 10.1093/aje/153.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Poliomyelitis in the Netherlands

Abstract: Despite a vaccination coverage rate of 97%, several poliomyelitis outbreaks occurred in the Netherlands during the last three decades, all among sociogeographically clustered, unvaccinated persons. Therefore, to eradicate polio, insight into poliomyelitis immunity is particularly useful. In 1995-1996, the authors conducted a population-based study and determined neutralizing antibodies against poliovirus types 1, 2, and 3 in 9,274 sera from the general population and from religious groups rejecting vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 13 publications
8
41
0
Order By: Relevance
“…The highest antibody seroprevalence and GMTs in each age group were for P2 and the lowest was for P3. These results are similar to those of other countries, such as Brazil (21), Germany (22), the United States (23), Italy (24)(25)(26)(27), Belgium (28), Greece (29), Netherlands (30), and South Africa (31). Nates and colleagues in Argentina found that humoral immunity to P3 declined significantly over time (32).…”
Section: Discussionsupporting
confidence: 87%
“…The highest antibody seroprevalence and GMTs in each age group were for P2 and the lowest was for P3. These results are similar to those of other countries, such as Brazil (21), Germany (22), the United States (23), Italy (24)(25)(26)(27), Belgium (28), Greece (29), Netherlands (30), and South Africa (31). Nates and colleagues in Argentina found that humoral immunity to P3 declined significantly over time (32).…”
Section: Discussionsupporting
confidence: 87%
“…This success has been achieved by maintaining high vaccination coverage (17,41). Similar to other countries, Switzerland before 2001 used mainly OPV.…”
mentioning
confidence: 99%
“…The values for seropositivity found in the various European surveys are generally satisfactory, ranging from 65.0% [4] to 100% [5] for poliovirus type 1, from 59% [4] to 100% [4,6,7] for poliovirus type 2 and from 40.0% [5] to 99.8% [8] for poliovirus type 3.…”
Section: Status Of Immunity In European Population Groupsmentioning
confidence: 92%
“…Roebuck et al [12] in Britain in 1982 attributed the modest level of protection (39%) in a group born between 1963 and 1968 to the shift from the inactivated poliovirus vaccine (IPV) schedule to oral poliovirus vaccine (OPV) which took place during that time, creating confusion over the number of doses necessary and a consequent lowering of the immunization rate. In Holland, Conyn-van Spaendonk et al [4] ascertained that in a population group with a low acceptance of the vaccine (around 30%) for religious reasons, the values of complete protection against polioviruses were very much lower compared with the rest of the national population. This situation serves to confirm the persisting risk of outbreaks of poliomyelitis if viruses are introduced, an event which occurred in 1978 and in 1992 in the group that refused the vaccination.…”
Section: Status Of Immunity In European Population Groupsmentioning
confidence: 99%